2003
DOI: 10.1152/jn.01096.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Disulfide Exerts Insecticidal Neurotoxicity Through Mitochondrial Dysfunction and Activation of Insect KATPChannels

Abstract: The plant-derived insecticides have introduced a new concept in insecticide research. In response to insect attacks, some plants can release volatile sulfur compounds such as dimethyl disulfide (DMDS) in the atmosphere, which are lethal for the generalist insects. We demonstrate that DMDS induced an uncommon complex neurotoxic activity. The studies of in vivo toxicity of DMDS in three insect species and mice indicated a highest bioactivity for insects. Although DMDS did not alter the electrophysiological prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 36 publications
2
57
2
2
Order By: Relevance
“…For example, tolbutamide reduces glucose availability to the glycolytic pathway, which in turn reduces the supply of pyruvate to the Kreb's cycle, resulting in decreased production of reduced NADH, and consequent decline in ⌬ m . Notably, one other report has demonstrated a neurotoxic effect that is induced via activation of neuronal KATP channels, and can be blocked by tolbutamide (52), which may be consistent with results shown in this work. Tat may also contribute to increased ⌬ m by other means, including inhibition of the mitochondrial F 1 F 0 -ATP-ase, or increasing electrochemical potential through increased production of (NADH) substrate.…”
Section: Mitochondrial Bioenergetics During Tat-induced Inflammation:supporting
confidence: 93%
“…For example, tolbutamide reduces glucose availability to the glycolytic pathway, which in turn reduces the supply of pyruvate to the Kreb's cycle, resulting in decreased production of reduced NADH, and consequent decline in ⌬ m . Notably, one other report has demonstrated a neurotoxic effect that is induced via activation of neuronal KATP channels, and can be blocked by tolbutamide (52), which may be consistent with results shown in this work. Tat may also contribute to increased ⌬ m by other means, including inhibition of the mitochondrial F 1 F 0 -ATP-ase, or increasing electrochemical potential through increased production of (NADH) substrate.…”
Section: Mitochondrial Bioenergetics During Tat-induced Inflammation:supporting
confidence: 93%
“…We believe that the border intercropping pattern was the best intercropping pattern of onion with lettuce because, first the caterpillar to enter in the field finds a barrier of onion crop and this attacks the onion, it begins to release a number of volatile organic compounds containing sulfur and these may have a defensive role. This hypothesis is congruent with Huang et al [22], Dugravot et al [23], Rouseff et al [24] and Auger et al [25], who have investigated the role of volatiles compounds released by Allium spp after damaged and those were classified as toxic or repellents for various insect pest. Mann et al [10], observed that Sulfur volatiles from Allium spp.…”
Section: Discussionsupporting
confidence: 83%
“…Tests in confined spaces have demonstrated that these products are highly toxic for various species (Auger and Thibout, 2002). One, dimethyl disulfide, interferes with the cytochrome oxidase mitochondrial complex involved in the production of ATP, thus causing a loss of neuronal activity and death in some species (Dugravot et al, 2003). Moreover, tests in natural settings on crucifers (Chew, 1988) have shown that sulfur compounds can act as chemical repellents against herbivores (Auger et al, 1989).…”
Section: Introductionmentioning
confidence: 99%